TI_GERICHTE 15.2009.127 vom 7. Dezember 2009 , Fallimento. Responsabilità dei creditori per le tasse e le spese scoperte - TI Tribunale d'appello (2009)
Fallimento. Responsabilità dei creditori per le tasse e le spese scoperte